“Tell me who you go with and I’ll tell you who you are” – Ideas for EFL teachers about collocations - Bailer, Cyntia; Marchi, Andreana (BELT - Brazilian English Language Teaching Journal, 2014)
<!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:PT-BR; mso-fareast-language:PT-BR; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page WordSection1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.WordSection1 page:WordSection1; –> Even though collocations are not known for some teachers by this name, they already take an important place in language teaching. In the past, language learning was thought and taught more as a matter of grammar study and vocabulary acquisition. With the growth of corpus linguistics, it is understood that this is not enough, but that it is also necessary to show students that even being grammatically correct, a sentence may not sound native-like if they do not use the right collocation. In this sense, collocations are a good way to empower and to enable students to master a foreign language skillfully. Under the light of some studies on collocations, this paper intends to describe these phenomena as well as to support English as a Foreign Language (EFL) teachers on applying collocations in their classes by giving starting ideas of its classroom use.